Educational Pain Points for Pediatric Brain Tumor Survivors: Review of Risks and Remedies - Peter L. Stavinoha; Thuy Trinh-Wong; Laura N. Rodriguez; Chawncey M. Stewart; Kris Frost (MDPI AG, 2021)
Evolving treatment paradigms have led to increased survival rates for children diagnosed with a brain tumor, and this has increasingly shifted clinical and research focus to morbidity and quality of life among survivors. Among unfavorable outcomes, survivors of pediatric brain tumors are at risk for academic failure and low educational attainment, which may then contribute to lower health related quality of life, lower income and vocational status, and a greater likelihood of dependence on others in adulthood. Several specific risk factors for lower educational performance and attainment have been investigated. These are typically examined in isolation from one another which clouds understanding of the full range and potential interplay of contributors to educational difficulties. This review integrates and summarizes what is known about the direct and indirect barriers to educational success and performance (i.e., educational pain points) to enhance clinician knowledge of factors to consider when working with pediatric brain tumor survivors. Specific barriers to educational success include neurocognitive difficulties, school absences, psychosocial challenges, challenges to knowledge and communication, and physical and sensory difficulties. Finally, we discuss the current state of educational interventions and supports and offer recommendations for future research to improve educational outcomes for pediatric brain tumor survivors.